Visions of Friendship and Equality: Representations of African Women in Missionary Propaganda in Interwar Britain - Hughes, Rebecca (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2013)
During the interwar years, British evangelical women began to promote African women as worthy of friendship and equality. These representations differed not only from Victorian images of African women, but also those popularized by interwar secular writers. This article argues that the two most prolific female missionary writers of the interwar period, Mabel Shaw and Cicely Hooper, promoted these positive images while working as educators of African women. As feminists, these evangelicals valued African women, and as adherents of fulfillment theology popularized in ecumenical missionary discourse, they admired features of African culture that they believed were divinely inspired. By the late 1920s, these missionary women generated even more favourable images of African women, as they feared Western materialism was disintegrating African home life. Thus, this article demonstrates the liminal position of missionary women tethered to audiences in Britain, Africa, and the growing ecumenical Church. It also points to the importance of the interwar years as a key period in which ideas about race, gender, and culture were being reworked. While these missionary women did not erase boundaries of difference between themselves and African women, they invited Britons to join them in building cross-cultural, cross-racial friendships.